The Retention of Collegiate Athletes as Minority Students and Future Teachers: A Case Study - McMillian, Martha (My University, 1987)
Today much attention is given to the recruitment of collegiate athletes, generally for the purpose of building strong athletic programs. Rarely is this recruitment seen as a possible means to boost affirmative action efforts to increase the number of minority students on our college campuses, or to assist in attracting minorities into professions in need of minorities, such as teaching. This paper presents a case study which outlines some concerns and problems as seen from the perspective of the coordinator of advisement services in a college of education at a large south-central university. This person serves as the advisor of approximately 45 collegiate athletes, many of whom are minority students contemplating careers in teaching. The problems fall into two basic categories: (a) the retention of minority collegiate athletes, and (b) the recruitment and retention of minority future teachers. Some possible solutions to these problems are outlined in the form of strategies for effective academic advisement, and possible means to dispel myths contributing to the low academic achievement of black athletes.
Keywords: race; demographics; teacher education; retention; eligibility